A BDI architecture for high level robot deliberation - Gottifredi, Sebastián (2008)
In this work we present a BDI agent architecture used for high level reasoning agents that control mobile robots that play soccer. This architecture is build on top of layered system, where each of these layers is associated with a di®erent level of abstraction. The proposed approach allows the speci¯cation of declarative goal driven robot behavior, that uses sophisticated high level reasoning and reactivity when needed. The elements of mental components are studied with their interaction and their syntaxis and semantics are de¯ned.